ANALYSIS OF JIGSAW LEARNING MODEL APPLICATIONS TO THE CONCEPTION OF BIOLOGY EDUCATION STUDENT - AWAL, RAUDHAH; AFIDAH, MAR'ATUL; WAHYUNI, SRI (Human Sustainability Procedia, 2018)
This study aimsto analyze the application of jigsaw learning model to the conception of Biology Education students about plant ecology. This research was conducted in FKIP Unilak in the6thsemester of the academic year2016/2017. The application of jigsaw learning model is given to Biology Education students who takethe ecology of plant subjects. The data collection technique is done by giving the concept test of ecologicalof plant, in the form of multiple choice written test equipped with the scale of confidence to answer test in the form of Certainty of Response Index. The test is done twice on the pretest and posttest. The data analyzed derived from multiple choice test results using Certainty of Response Index. The results of data analysis can identify conceptions that occur in students who are grouped on the konwledge of correctconcept, lucky guessing, misconception, and lack of knowledge on the course of plant ecology. The result of the research found that the basic biology conception ofUnilak FKIP biology students has misconception. The basic conception of biology consists of the concept of the ecology concept of subconscope subfields of terrestrial biomes of students with misconceptions of48.75%. This is derived from 240 conception events that occurred in 16 students of Biology Education Unilak FKIP.